Effects of plyometric training and beta-alanine supplementation on maximal-intensity exercise and endurance in female soccer players - Rosas, F.; Ramirez-Campillo, R.; Martinez, C.; Caniuqueo, A.; Canas-Jamet, R.; McCrudden, E.; Meylan, C.; Moran, J.; Nakamura, F. Y.; Pereira, L. A.; Loturco, I.; Diaz, D.; et al. (Journal of Human Kinetics, 2017)
Plyometric training and beta-alanine supplementation are common among soccer players, although its combined use had never been tested. Therefore, a randomized, double-blind, placebo-controlled trial was conducted to compare the effects of a plyometric training program, with or without beta-alanine supplementation, on maximal-intensity and endurance performance in female soccer players during an in-season training period. Athletes (23.7 ± 2.4 years) were assigned to either a plyometric training group receiving a placebo (PLACEBO, n = 8), a plyometric training group receiving beta-alanine supplementation (BA, n = 8), or a control group receiving placebo without following a plyometric training program (CONTROL, n = 9). Athletes were evaluated for single and repeated jumps and sprints, endurance, and change-of-direction speed performance before and after the intervention. Both plyometric training groups improved in explosive jumping (ES = 0.27 to 1.0), sprinting (ES = 0.31 to 0.78), repeated sprinting (ES = 0.39 to 0.91), 60 s repeated jumping (ES = 0.32 to 0.45), endurance (ES = 0.35 to 0.37), and change-of-direction speed performance (ES = 0.36 to 0.58), whereas no significant changes were observed for the CONTROL group. Nevertheless, compared to the CONTROL group, only the BA group showed greater improvements in endurance, repeated sprinting and repeated jumping performances. It was concluded that beta-alanine supplementation during plyometric training may add further adaptive changes related to endurance, repeated sprinting and jumping ability.